Needs Analysis Of Development Of Product-Based Learning Models With Teaching Factory Approach - et al., John Friadi (International Journal of Advanced Science and Technology, 2020)
This research is an analysis of preliminary research needs in the development of a product-basedlearning model with a teaching factory approach using the ADDIE method (Analyze, Design,Development, Implement, Evaluation). This study aims to measure the level of needs analysis of thedevelopment of product-based learning models with a teaching factory approach characterized bydistributing needs analysis questionnaires. There are 3 (two) objectives that are sought, namelymeasuring the level of need for product-based learning models from the perceptions of students,teachers and industry practitioners, measuring learning experiences and the need to develop a productbased learning model with a teaching factory approach. Descriptive quantitative analysis models areused to supplement this research with research input in the form of questionnaires. The closed questionquestionnaire method is used to get the level of perception of model needs by using yes and no answerchoices with the level of model needs of students coming from twenty students (20), while the level ofneeds of the teacher model comes from five (5) teachers and the level of need of the practitioner'sperception model Industry comes from five (5) industrial practitioners. The results of the calculation ofthe level of perception needs of students, teachers and industry amounted to 84.17% (very needy), thelearning experience amounted to 66.07% (needy) and the level of need for developing learning modelswas 90.74% (very needy).